Milkfish Ponds As a Local Economis Base in Improving Community Welfare - Puspitasari, Lisa; Nurhidayati, Safitri; Syam, Irma (Gorontalo Development Review, 2025)
Coastal areas have the potential to develop the regional economy through the fisheries sector. The fisheries sector can be developed through milkfish farming. Milkfish farming plays a role in creating employment opportunities. Milkfish farming is not only a main source of livelihood but also a driving force for the local economy. This study aims to identify and describe the role of milkfish pond potential in improving the welfare of coastal communities in terms of strengthening the local economic base. Community welfare is shaped by improvements in the economy, education, health, and other social aspects. This study uses a qualitative approach with a case study method. Data was collected through interviews, field observations, and documentation conducted in Kasai Village, Derawan Islands, with a total of three milkfish pond farmers and one village official as informants. The results show that milkfish pond farming can contribute to improving the standard of living of local communities, especially in coastal areas. Through this business, daily needs can be met, education costs can be covered, and health can be improved. Milkfish farming also absorbs local labor. However, there are challenges in managing milkfish farming businesses, namely limited knowledge of human resources in terms of increasing production, limited marketing, and selling prices. Through these efforts, daily needs can be met, education costs can be covered, and health can be improved. Milkfish ponds also absorb local labor. However, there are challenges in managing milkfish ponds, namely limited knowledge among human resources in terms of increasing production, limited marketing, uncertain selling prices, and the lack of diversification of processed food products from milkfish. As a basis for the local economy to support the village economy, milkfish ponds require full support from the local government in terms of capital and training in production capacity improvement and marketing strategies so that milkfish pond businesses can contribute in the long term to the economic resilience of the village.